Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1152/ajpendo.00419.2004
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal adipose tissue cytokine gene expression: relationship to obesity and metabolic risk factors

Abstract: Adipose tissue is a major source of inflammatory and thrombotic cytokines. This study investigated the relationship of abdominal subcutaneous adipose tissue cytokine gene expression to body composition, fat distribution, and metabolic risk during obesity. We determined body composition, abdominal fat distribution, plasma lipids, and abdominal subcutaneous fat gene expression of leptin, TNF-␣, IL-6, PAI-1, and adiponectin in 20 obese, middle-aged women (BMI, 32.7 Ϯ 0.8 kg/m 2 ; age, 57 Ϯ 1 yr). A subset of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
1
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 45 publications
(60 reference statements)
12
99
1
12
Order By: Relevance
“…[4][5][6] Our findings of a negative association between waist circumference and mRNA levels of adiponectin are in line with previous reports that showed adiponectin gene expression to be lower in obese subjects with abdominal obesity than in those with subcutaneous obesity. 2,4,5,21 As expected, and in agreement with previous reports, 22,23 we observed a significant association between BMI, waist and insulin resistance as assessed by HOMA, as well as between BMI, waist and hs-CRP. 1,24 A strong association between inflammation and obesity has been previously observed 1 and high levels of hs-CRP were reported in 35% of men and 60% of women with a BMI higher than 30 kg/m 2 .…”
Section: Adiponectin Gene Expression In Human Adipocytes M Zamboni Et Alsupporting
confidence: 93%
“…[4][5][6] Our findings of a negative association between waist circumference and mRNA levels of adiponectin are in line with previous reports that showed adiponectin gene expression to be lower in obese subjects with abdominal obesity than in those with subcutaneous obesity. 2,4,5,21 As expected, and in agreement with previous reports, 22,23 we observed a significant association between BMI, waist and insulin resistance as assessed by HOMA, as well as between BMI, waist and hs-CRP. 1,24 A strong association between inflammation and obesity has been previously observed 1 and high levels of hs-CRP were reported in 35% of men and 60% of women with a BMI higher than 30 kg/m 2 .…”
Section: Adiponectin Gene Expression In Human Adipocytes M Zamboni Et Alsupporting
confidence: 93%
“…27 Although visceral fat decreased in HI, the lack of a change in abdominal subcutaneous fat in either exercise training group may be linked to a negligible or nonexistent change in adiponectin, due to the strong relationship between abdominal fat deposition and the dysregulation of adiponectin gene expression in adipose tissue. 10 It is also interesting that an inverse relationship between adiponectin mRNA expression and tumor necrosis factor-α (TNF-α) has been demonstrated, potentially substantiating the importance of adiponectin as a suppressive mediator of proinfl ammatory cytokines. 28 In short-term aerobic exercise training studies that incorporated a variety of exercise modalities, Bluher et al demonstrated improvements in plasma adiponectin and Adipo R1/R2 mRNA expression without weight loss in persons with impaired glucose tolerance and T2D.…”
Section: Peak Oxygen Consumption and Maximum Work Outputmentioning
confidence: 99%
“…10 This is important because adiponectin has been shown to improve informed consent prior to screening and study participation, and all study procedures were approved by the Institutional Review Board of the University of Arkansas for Medical Sciences and the Central Arkansas Veterans Healthcare System Research and Development Committee.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating mononuclear cells from obesity causes inflammation, which, in turn, may cause diseased states such as diabetes. 1 You et al 2 further demonstrated an increased pro-inflammatory cytokine production in obese humans, particularly in abdominal adipose tissue. Different approaches for controlling the obesity epidemic include expanding education programs about healthy living, reducing the marketing of unhealthy, high-fat foods, and providing low-cost exercise programs.…”
Section: Introductionmentioning
confidence: 95%